Trust in blockchain-based systems - Moritz Becker; Balázs Bodó (Internet Policy Review, 2021)
Trust can best be understood as a relational attribute between (1) a social actor and other actor(s) (interpersonal trust) and / or (2) actors and institutions (institutional or systemic trust) and (3) institutions and (trusting) actors (trust as shared expectations), where institutional frameworks define the nature and strength of trust relationships between different actors.
Keywords: 300; Trust; Blockchain